A Comparative Analysis of Amytripiline, Flunnarazine and Topiramate in the treatment of Primary Headache (Nepal Journal of Neuroscience, 2021)
Introduction Primary headache disorder, characterized by recurrent headache is the mostprevalent disease leading to widespread ill health and impaired quality of life.In Nepal headache is one of the most common cause of patient attending neurologyclinic. Amitriptyline, Flunarizine and Topiramate are common drugs in thetreatment of primary headache. We conducted this study to compare the efficacy of drugs namely Amitriptyline, Flunarizine and Topiramate in the treatment of primary headacheMaterials and MethodsThis is the retrospective data analysis of primary headache patient treated withamitriptyline, flunarizine and topiramate. On their first, second andthird subsequent visits, Headache Impact Test 6 Scoring was done by a medicalperson. Patient were treated clinically. After third follow up data wereanalyzed using SPSS version 20.0. Categorical variables were compared bychi-square test, paired sample t-test, ANOVA test and Welch test.ResultsA total of 142 patient data was analyzed. The most common age group werebetween 20 to 39 years (56.34%) followed by 40 to 59 years (33.80%). Female werepredominant in the group 124 (87.32%).  All three medication Amitriptyline,Flunarizine and Topiramate were able to significantly lower Headache impact test -17.23 ± 6.643, -14.06 ± 7.155, -15.82 ± 5.907 respectively (P-